Factores que inciden en los niveles de estrés y ansiedad en los Policías del grupo operativo Gudmo Deval del Comando Departamento principal del municipio de Palmira (2024)
This research examines the impact of stress and anxiety on police personnel, addressing serious mental health issues such as depression, post-traumatic stress and suicidal thoughts, particularly in Colombia, where the work environment presents significant challenges. The demands of work in violent contexts cause a high level of stress, which is reflected in an increase in sick leave requests for mental health reasons.